Factor analysis of the incidence of ARI in Toddlers during the Covid-19 Pandemic - Kartinazahri (Science Midwifery, 2022)
Acute respiratory infections (ARIs) are one of the leading causes of death among children in developing countries. Acute respiratory infection (ARI) is a disease that affects one or more parts of the airway from the nose to the alveoli, including the appendages (sinus, middle ear cavity, pleura). The high incidence of acute respiratory infections in children under five years of age is a serious problem that needs to be addressed immediately. The aim of this review study was to analyze the causes of acute respiratory infections in children under five years of age. This study is a systematic review using online databases namely Scholar, ScienceDirect, and ProQuest. The keywords used were ARI, infant, and the Covid-19 pandemic. The selection process used the PRISMA protocol, resulting in 15 articles that met the inclusion criteria. The 15 articles included factors such as environmental influences, ventilation, physical environment, mothers' knowledge, population density, indoor air pollution, and children not receiving full immunization. The impact of the COVID-19 pandemic in several parts of Indonesia has the potential to hinder maternal and child access to health services ARI as the government implements policy-based movement restrictions. The impact of the Covid-19 pandemic that has occurred has been a reduction in public access to health facilities in Posyandu and Puskesmas, such as the implementation of primary immunizations, weighing and measuring the height of children under 5 years of age, which have not been controlled.